Core Steps to the Azaphilone Family of Fungal Natural Products. (9th July 2021) - Williams, Katherine; Greco, Claudio; Bailey, Andrew M.; Willis, Christine L.
Abstract: Azaphilones are a family of polyketide‐based fungal natural products that exhibit interesting and useful bioactivities. This minireview explores the literature on various characterised azaphilone biosynthetic pathways, which allows for a proposed consensus scheme for the production of the core azaphilone structure, as well as identifying early diversification steps during azaphilone biosynthesis. A consensus understanding of the core enzymatic steps towards a particular family of fungal natural products can aid in genome‐mining experiments. Genome mining for novel fungal natural products is a powerful technique for both exploring chemical space and providing new insights into fungal natural product pathways. Abstract : Azaphilones are a polyketide‐based family of fungal natural products with a highly oxygenated bicyclic pyrone‐quinone structure, many of which have useful and interesting bioactivities. This minireview reveals the common steps in azaphilone biosynthetic pathways to aid the use of genome mining to identify orphan azaphilone biosynthetic gene clusters.